The Result of Enhancing the Value of Careful Reading on Reading Achievement in Fourth Graders - Bly, Brittany Dianne (2019)
Researchers and educators agree that reading comprehension and interest in reading are strong predictors of future success in academics. I studied the effects of establishing interest for reading (i.e. increased reinforcement value for reading) and reading achievement with 4th grade students. In Experiment I, I tested the correlations between a measure of reinforcement value for reading level (determined by a 20-min, 10s whole interval probe session) and reading achievement tests of 30 fourth-grade students. The reading achievement tests measured passage comprehension, literary comprehension, informational comprehension, and vocabulary. I found significant correlations between reinforcement value for reading and all reading achievement measures. In Experiment II, using a pre- and postintervention design with a multiple probe logic, I tested the effects of establishing a level of interest in reading (CR+ for reading) through a 4-step, peer-collaborative procedure on reading achievement outcomes for 6 fourth grade students. The 4-step procedure included 1) shared reading period, 2) vocabulary task 3) independent reading period, and 4) a comprehension drawing task. The establishment of CR+ for reading in all 6 participants resulted in grade-level increases from 0.8-4.1 in WJ-IV passage comprehension, -0.4- 2.3 in WJ-IV vocabulary, and 0.2-2.3 in Gray Silent Reading Tests (GSRT). In Experiment III, I conducted a component analysis to test the significance of the independent and shared reading component of the 4-step peer-collaborative procedure. Using a simultaneous treatment design with a built-in crossover, I studied the effects a Collaborative Independent Reading Treatment (CIR) and Collaborative Shared Reading Treatment (CSR) on establishing CR+ for Reading and the overall effect it had on reading achievement. The 4-step peer-collaborative procedure was the same except students were either exposed to only shared or independent reading and not the other. Participants were yoked into dyads across treatment conditions and completed intervention with a partner in the same treatment condition. Participants in the CIR treatment met CR+ for reading in 1 phase while participants in the CSR treatment did not meet CR+ for reading in 1 phase. The establishment of CR+ for reading in the CIR treatment group resulted in grade-level increases from 1.2 to 3.4 in the WJ-IV passage comprehension, 0.4 to 4.5 in the WJ-IV vocabulary, and -1.2 to 4.3 in the GSRT. Without the establishment of CR+ for reading in the CSR treatment group, grade-level increases for WJ-IV passage comprehension was -1 to 2.1, WJ-IV vocabulary was -0.9 to 0, and GSRT was -0.3 to 1.5). I conducted a crossover treatment where participants in the CSR treatment group underwent the CIR treatment procedure. All 4 participants acquired CR+ for reading in 1 phase of the intervention and increases were 0.6 to 2.2 for WJ-IV passage comprehension, 0.8 to 4.3 for WJ-IV vocabulary, and -0.5 to 2.7 for GSRT. The CIR treatment procedure was more effective in, not only establishing reinforcement value for reading, but also in increasing reading achievement in a very short amount of time.